2017
DOI: 10.1017/sjp.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Nonsymbolic and Symbolic Comparison Tasks in School-Aged Children

Abstract: Basic numerical processing has been regularly assessed using numerical nonsymbolic and symbolic comparison tasks. It has been assumed that these tasks index similar underlying processes. However, the evidence concerning the reliability and convergent validity across different versions of these tasks is inconclusive. We explored the reliability and convergent validity between two numerical comparison tasks (nonsymbolic vs. symbolic) in school-aged children. The relations between performance in both tasks and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(98 reference statements)
0
3
0
2
Order By: Relevance
“…Research conducted in Chile has also addressed the evaluation of basic numerical skills (Castro, Estévez, Gómez, & Dartnell, 2017b; Sepúlveda, Rodríguez, & Peake, 2020), and the study of strategies and calculation errors (Cerda, Flores, & Pérez, 2015; Gálvez et al, 2011).…”
Section: Research On Numerical Cognition In Chilementioning
confidence: 99%
See 4 more Smart Citations
“…Research conducted in Chile has also addressed the evaluation of basic numerical skills (Castro, Estévez, Gómez, & Dartnell, 2017b; Sepúlveda, Rodríguez, & Peake, 2020), and the study of strategies and calculation errors (Cerda, Flores, & Pérez, 2015; Gálvez et al, 2011).…”
Section: Research On Numerical Cognition In Chilementioning
confidence: 99%
“…Similar processes have been studied with older children. Castro et al (2017b) evaluated the performance of students from grades 1 to 6 in primary school using symbolic and non-symbolic comparison tasks and their relation with mental arithmetic calculation. The results showed that both comparison tasks were highly correlated and predicted arithmetic performance, suggesting that both symbolic and non-symbolic comparison tasks evaluated the approximate representation system, while simultaneously predicting performance in arithmetic calculation.…”
Section: Research On Numerical Cognition In Chilementioning
confidence: 99%
See 3 more Smart Citations